Decidual/placental and first trimester plasma levels of hsa-miR-199a-3p|hsa-miR-199b-3p and hsa-miR-3150b-3p are associated with insulin secretion in pregnancy - Taschereau, Amélie; White, Frédérique; Allard, Catherine; Edlow, Andrea G.; Aguet, François; Ardlie, Kristin G.; Florez, Jose C.; Jacques, Pierre-Étienne; Karumanchi, S. Ananth; Powe, Camille E.; Bouchard, Luigi; Hivert, Marie-France (Frontiers in Endocrinology, 2025)
Background/AimsThe placenta expresses and releases specific microRNAs (miRNAs) into the maternal circulation that may influence insulin secretion during pregnancy. We hypothesized that specific decidual/placental miRNAs are associated with maternal insulin secretion during pregnancy.MethodsIn the Genetics of Glucose regulation in Gestation and Growth (Gen3G) prospective cohort, we estimated maternal insulin secretion using the Stumvoll first phase index derived from an oral glucose tolerance test at ~26 weeks of gestation. We quantified miRNAs by small RNA sequencing in placenta (N=435) and first trimester plasma (=422) samples. We used the Limma R package to identify miRNAs associated with the Stumvoll index (P<0.05). We adjusted models for Matsuda index, gravidity, maternal age, newborn sex, gestational age at sampling (first trimester plasma sampling or delivery for placenta samples), and for technical covariates (batch and run for plasma, surrogate variables for placenta).ResultsParticipants had a median [IQR] Stumvoll first phase index of 1112.9 [905.4 - 1284.5] in pregnancy. We identified 30 decidual/placental and 93 first trimester plasma miRNAs nominally associated with the Stumvoll first phase estimate (P<0.05). Lower insulin secretion was associated with lower levels of has-miR-199a-3p|has-miR-199b-3p (b=1.47 [0.10, 2.69] in placenta and b= 4.22 [0.70, 7.67] in plasma), and with higher levels of has-miR-3150b-3p (b= -6.97 [-14.39, 0.40] in placenta and b= -9.19 [-18.38, -0.60] in plasma).ConclusionWe identified hsa-miR-199a-3p|hsa-miR-199b-3p and hsa-miR-3150b-3p as differentially expressed in placenta and circulating levels associated with insulin secretion in pregnancy. Hsa-miR-199a-3p may regulate insulin secretion by modulating the expression of E-cadherin and components of the Notch signaling pathway; hsa-miR-3150b-3p may influence glucose-induced insulin secretion through interaction with phospholipase A2.